Enhancing the Counseling Process: The Significance of Counselor's Personality Traits - Sari, Mustika; Karneli, Yeni; Hariko, Rezki (Guidance and Counseling Study Program, Pattimura University, 2024)
This paper examines the significance of counselor's personal qualities in the counseling process. The research highlights the impact of counselor's personality on counseling attitudes and behaviors, emphasizing the counselor's role in establishing a strong counseling relationship. The study draws on a literature review of selected articles and scientific papers to explore the relationship between counselor's personal qualities and the effectiveness of counseling services. The findings indicate that the success of the counseling process is highly dependent on the counselor's personal characteristics, which include empathy, respect, acceptance, appreciation, and honesty. Furthermore, the quality of the counseling relationship, characterized by the interaction between the counselor and the individual seeking guidance, plays a pivotal role in achieving positive counseling outcomes. The research underscores the importance of counselor's personal qualities in shaping the counseling experience and highlights the need for counselors to possess desirable character traits. The implications of this study extend to counselor training programs and professional development, emphasizing the significance of nurturing and enhancing counselor's personal qualities to provide effective counseling services.